ANALISIS PENJUALAN KULINER SECARA ONLINE MELALUI APLIKASI - Lailatun Nafisa (Institut Teknologi dan Bisnis Yadika, 2021)
In the current pandemic period, many people are experiencing an economic downturn, especially in Bangil’s culinary area, so business people must rack their brains on how to keep them selling and promoting their products. The purpose of this research is to find out how effective online sales are through the application and to analyze the advantages and disadvantages of the application. This Research Uses Interview Method Where The Informants Are Culinary MSME Actors In Bangil Area The Researchers Take Only 7 People. The result of this research is that MSMEs are very helpful in sales and promotion through the application, with the application they can attract more customers, it doesn’t need to spend too expensive promotion costs. By using the application, there are many benefits, although there are some drawbacks, but these weaknesses have no effect on MSMEs. The applications use include Shopee-Food, Grab-Food, Nu-Food and so on.